Diet diversity, individual heterozygosity and habitat heterogeneity influence health parameters in Eurasian Kestrels (Falco tinnunculus) - Hochleitner, Lukas; Korpimäki, Erkki; Chakarov, Nayden; Isaksson, Caroline; Nebel, Carina; Renner, Swen C.; Vasko, Ville; Voigt, Christian C.; Terraube, Julien; Sumasgutner, Petra (Institute of Physics Publishing, 2025)
The loss of habitat heterogeneity due to agricultural intensification has led to a global decline in farmland birds. Among them is the Eurasian Kestrel Falco tinnunculus, which occupies high trophic levels and may be adversely affected by reduced food quantity or quality and consequent health impacts. In this study, we investigate the effects of habitat heterogeneity, individual heterozygosity and diet diversity on five different health indices (integument coloration, dietary antioxidants, haematocrit, body condition and parasite infection). The study was conducted in farmland areas of western Finland during a year of exceptionally low vole abundance. We found no obvious relationship between diet diversity and habitat heterogeneity. An interaction between diet diversity and individual heterozygosity in females suggested that diet specialists were able to maintain more intensely coloured integuments only if they had higher genetic diversity. In addition, more heterozygous females were less likely to be infected with Haemoproteus than females with lower individual genetic diversity. Finally, specialist males with lower diet diversity had higher body condition than males with a more generalist diet. Our results suggest that variation in individual quality and foraging ecology should be considered in conjunction with spatial variation in habitat heterogeneity to understand sex-specific variation in kestrel health. These findings add to a better understanding of the mechanisms linking land-use change to health indices in a common avian predator, which can be used as a health sentinel in European agroecosystems.